Growth of Student Creativity through Extracurricular Activities at Elementary School Laboratory of Universitas Pendidikan Indonesia Cibiru Campus - Fani Widia Putri; Dede Margo Irianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Extracurricular activities have an important role in the process of character education, especially character building in elementary school students. From several extracurriculars in SD Laboratory such as scouts, paskibra, crafts, and dance, this is an alternative extracurricular program that can grow and awaken students' creative spirit. Scout, paskibra, craft, and dance extracurricular training activities can help students to be able to develop their abilities. Students can express themselves through marching exercises, creating pioneering works, dancing, and many other interesting activities. In terms of education, character education is needed to instill a creative and critical attitude in students. However, the space for creative ideas for students is still not optimal. For this reason, the existence of extracurricular activities provides space for students to know how to implement, plan, implement, and evaluate activities in growing student creativity through routine exercises in extracurricular activities. Through a qualitative approach, this study seeks to find ways to find out what efforts can be made to foster students' creativity through extracurricular activities at Laboratory Elementary Schools. Data obtained through observation techniques, interviews, and documentation. Then the data was obtained which was then analyzed using a type of qualitative analysis.